PERAN MASYARAKAT DALAM MEMBENTUK LEARNING SOCIETY - Wathoni, Kharisul (IAIN Ponorogo, 2011)
A discussion of the learning society has been issued by Torsten Husen in 1971. Learning society is the empowerment of communities and families in education. Within this time, the role of community and family in formal educational institutions has still lack of attention. Since the existence of school is in the midst of the society, certainly it should be an integral part of the surrounding community and it must not be moving around in the void of social life. Learning society is an effort to increase public participation in the management of learning resources provided in the community, hence this system may not be separated or remain an integral part of society as a whole. Through the efforts of this community empowerment, educational institutions plays an important role as the core of the learning society that can result in graduates who are qualified, capable, functional, and integrated with the community.Â ÙÙÙØ¯ ÙØ§Ù ØªÙØ±Ø³ØªÙÙ ÙÙØ³ÙÙ Ø¨Ø§ÙØªØ¹Ø±ÙÙ Ø¹Ù Ø§ÙÙ Ø¬ØªÙ Ø¹ Ø§ÙÙ ØªØ¹ÙÙ Ø³ÙØ© 1971 Ù . ÙØ§ÙÙ Ø¬ØªÙ Ø¹ Ø§ÙÙ ØªØ¹ÙÙÙ ÙÙ ØªÙÙÙØ© Ø§ÙÙ Ø¬ØªÙ Ø¹ ÙØ§ÙØ£Ø³Ø±Ø© ÙÙ Ø§ÙØªØ±Ø¨ÙØ©. Ø¥ÙÙ Ø§ÙØ¢ÙØ ÙÙ ÙÙÙ ÙÙØ§Ù Ø§ÙØªÙ Ø§Ù ÙØ§Ù Ø¨Ø¯ÙØ± Ø§ÙÙ Ø¬ØªÙ Ø¹ ÙØ§ÙØ£Ø³Ø±Ø© ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ±Ø³Ù ÙØ© ( Ø§ÙÙ Ø¯Ø§Ø±Ø³). ÙÙÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ ÙÙ ÙØ³Ø· Ø§ÙÙ Ø¬ØªÙ Ø¹Ø ÙØ§Ø¨Ø¯ ÙÙ Ø£Ù ØªÙÙÙ Ø¬Ø²Ø¡Ø§ ÙØ§ ÙØªØ¬Ø²ÙØ¡ Ù Ù Ø§ÙÙ Ø¬ØªÙ Ø¹Ø ÙÙØ§ ØªØ®Ø±Ø¬ Ø¹Ù Ø§Ø·Ø§Ø± Ø§ÙØÙØ§Ø© Ø§ÙØ§Ø¬ØªÙ Ø§Ø¹ÙØ©.Ø§ÙÙ Ø¬ØªÙ Ø¹ Ø§ÙÙ ØªØ¹ÙÙ ÙÙ Ø§ÙÙ ØØ§ÙÙØ© ÙØªØ±ÙÙØ© Ù Ø´Ø§Ø±ÙØ© Ø§ÙÙ Ø¬ØªÙ Ø¹ ÙÙ Ø¥Ø¯Ø§Ø±Ø© Ù ØµØ§Ø¯Ø± Ø§ÙØªØ¹ÙÙÙ Ø§ÙÙ ÙØ¬ÙØ¯Ø© ÙÙ Ø§ÙÙ Ø¬ØªÙ Ø¹ ÙØ§Ø³ØªÙØ§Ø¯ØªÙØ§Ø ØØªÙ ÙØ§ ÙÙÙÙ ÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙØ© Ù ÙÙØµÙØ§ Ø£Ù ÙÙ Ø«Ø§Ø¨Øª ÙÙ ÙÙÙÙ Ø¬Ø²Ø¡Ø§ ÙØ§ ÙØªØ¬Ø²ÙØ¡ Ù Ù Ø§ÙÙ Ø¬ØªÙ Ø¹. Ø¨Ù ØØ§ÙÙØ§Øª Ø§ÙØªÙÙÙØ© Ù Ø§ÙØªØ±ÙÙØ© ÙØ°ÙØ Ø£ØµØ¨ØØª Ø§ÙÙ Ø¤Ø³Ø³Ø§Øª Ø§ÙØªØ±Ø¨ÙÙØ© Ù Ø±ÙØ²Ø§ ÙÙÙ Ø¬ØªÙ Ø¹ Ø§ÙÙ ØªØ¹ÙÙ ØØªÙ Ø®Ø±ÙØ¬Øª Ø§ÙØ®Ø±ÙÙØ¬ÙÙ Ø§ÙØ¬ÙÙØ¯ÙÙ Ù Ø°ÙÙ Ø§ÙÙÙØ§ÙØ§Øª Ø§ÙÙØ¸Ø§Ø¦ÙÙØ© Ø§ÙÙ ØªØØ¯ÙÙ Ø¨Ø§ÙÙ Ø¬ØªÙ Ø¹.Â Â Â